Human autonomy in cross-cultural context perspectives on the psychology of agency, freedom, and well-being - Chirkov, Valery I.; Ryan, Richard M; Sheldon, Kennon M (Springer eBook., 2011)
Collection of multi-disciplinary essays explores the nature of personal autonomy, considering its developmental origins, its expression within relationships, its importance within groups and organizational functioning, and its role in promoting the democratic and economic development of societies. In Human Autonomy in Cross-Cultural Context: Perspectives on the Psychology of Agency, Freedom, and Well-Being, the starting point for all essays is self-determination theory, which is an integrated theory of human motivation and healthy development that has been under development for more than three decades. From there, the essays go on to provide the following: a theoretical and conceptual account of the nature and psychological mechanisms of personal motivational autonomy and human agency; rich, multidisciplinary empirical evidence supporting the claims and propositions about the nature of human autonomy and capacities for self-regulation; explanations of how and why different psychological and socio-cultural conditions may play a role in promoting or undermining people's autonomous motivation and well-being; and discussions of how the promotion of human autonomy can positively influence environmental protection, democracy promotion and economic prosperity. While the topics in this text are varied, the authors all share a vision that human autonomy is a fundamental pre-condition for both individuals and groups to thrive. They also collectively believe that without understanding the nature and mechanisms of autonomous agency, vital social and human problems cannot be satisfactorily addressed